THE EFFECT OF INVESTMENT DECISIONS, FUNDING DECISIONS, AND PROFITABILITY ON MANUFACTURING COMPANY VALUE IN INDONESIA STOCK EXCHANGE 2015-2018 PERIOD - Sumarau, Swingly Kellen (ACCOUNTABILITY, 2019)
The main objective of company is maximizing company value or wealth for stockholders. The company also could showing value assets owned by company. More and more high value company then more and more high prosperity received by stockholders. The most determinant factors which indicate affect company value are decision investment, decision funding, and profitability. This study uses secondary data such as financial report that published on the Indonesia Stock Exchange and Central Bank of Indonesia during period of 2015-2018. This study intend quantitative approach and conducts multiple regression. This study composes dependent variable is value company whereas independent variable are investment decision, decision funding, and profitability. Results of this study show that in a manner partial decision investment take effect positive and not significant to value company. Decision investment, decision funding, and profitability in a manner simultaneous take effect significant to value company.